Promoting mental health in the workplace: web software development and validation - Evelin Daiane Gabriel Pinhatti; Regina Celia Bueno Rezende Machado; Rosangela Aparecida Pimenta; André Estevam Jaques; Maria do Carmo Fernandez Lourenço Haddad (Universidade de São Paulo, 2024)
Objective to develop and validate the content and technical aspects of a web software program for promoting mental health in the workplace. Method: applied methodological study and technological development, carried out in three stages: 1) Umbrella review development; 2) Web software development; 3) Content and technical validation carried out by 14 judges. The data was submitted to descriptive statistical analysis and calculation of the content validity index. Results: based on the guidelines' recommendations, information was defined and extracted in order to develop the web software consisting of the following dimensions: mental health education, support among coworkers, promotion strategies and mental health self-assessment. For the technical development, the objectives, general functions and technological infrastructure were defined. After development and functional testing, the version was made available for content and technical validation by judges. The overall content validity index was 0.98 and for the technical aspects it was 0.97. Conclusion: the agreement between the judges in relation to the content and technical aspects, as well as the suggestions incorporated, demonstrated the potential for using web software to promote mental health in the workplace.